Preliminary Study on The Effect of Inlet Pressure of Standard Slit Interdigital Micro Mixer Towards Mixing by Computational Fluid Dynamics - Ahmad Termizi, Siti Nor Azreen
The aim of this work is to visualize the velocity profile and concentration profile of the mixing element of standard slit interdigital micro mixer (SSIMM) by simulating it in computational fluid dynamic (CFD).